A Novel Polysaccharide From Heimioporus retisporus Displays Hypoglycemic Activity in a Diabetic Mouse Model - Feng, Xiaobin; Wang, Peng; Lu, Yuxiao; Zhang, Zejun; Yao, Chunxin; Tian, Guoting; Liu, Qinghong (Frontiers in Nutrition, 2022)
A novel polysaccharide (HRP) was extracted from the edible mushroom Heimioporus retisporus. HRP had weight-average molecular weight 1,949 kDa and number-average molecular weight 873 kDa, and its major components were arabinose (0.71%), galactose (12.93%), glucose (49.00%), xylose (8.59%), mannose (17.78%), and glucuronic acid (10.99%). FT-IR spectroscopy and NMR spectroscopy revealed that HRP was composed of 1,3-linked β-D-glucose, 1,6-linked β-D-mannose, 1,6-linked β-D-galactose, 1,4-linked β-D-galactose, 1,4-linked β-D-xylose, and 1,5-linked α-L-arabinose. Thermogravimetric analysis indicated that degradation temperature (T0) of HRP was 200 °C. In an STZ-induced diabetic mouse model, oral administration of HRP (40 mg/kg/d) for 28 days significantly reduced blood glucose levels, and reduced heart organ index by decreasing expression of IL-6 and TNF-α. Our findings indicate hypoglycemic effect of HRP, and its potential application as a hypoglycemic agent.